Chemical composition of essential oil of nutmeg (Myristicafragrans Houtt.) accesc sions - Krishnamoorthy, K M Maya, T John Zachariah, B (Journal of Spices and Aromatic Crops, 2004)
Sixty-five nutmeg (Myristica fragrans) germplasm accessions from Indian Institute of Spices Research, Experimental Farm, Peruvannamuzhi (Kerala), were evaluated for chemical composition of essential oil of nJltmeg and mace and variability was observed among the accessions. The major constituents of significance in the essential oil were sabinene, safrole, myristicin and elemicin. Among the accessions, A9/71 and A9/95 had high sabinene and low hallucinogens namely, myristicin, elemicin and safrole, in both nutmeg and mace oils.